Will the German Debt Brake Succeed? Survey Evidence from State Politicians - Frank Streif; Friedrich Heinemann; Eckhard Janeba; Christoph Schröder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The present paper analyzes expectations of German politicians about the German debt brake (Schuldenbremse), which became part of the German constitution in 2009. This fiscal rule requires the federal government and the German states to run a (cyclically adjusted) budget deficit of no more than 0.35% of GDP starting in 2016 and zero % starting in 2020, respectively. We use unique survey data from more than 630 politicians at the state level to systematically study the subjective beliefs in the compli-ance and desirability of the debt brake. We find that i) state politicians who belong to the coalition parties of the current federal government coalition believe more strongly in federal government compliance, ii) state politicians who belong to the party of the current state government believe more strongly in the own state s compliance, iii) worse state fiscal conditions and stronger beliefs in lack of credible enforcement of the debt brake lower the perceived likelihood of compliance, iv) there often is a large discrepancy in the assessed probability of compliance between politicians from the own state vs. politicians from other states, v) beliefs into the consequences of non-compliance with the debt brake are quite heterogeneous, and vi) politicians often find the debt brake more desirable than probable.
Keywords: H60; H70; H77; 330